Study on the Adaptability of 'Huangguogan' in Jiangyou, Sichuan Province. Issue 3 (April 2020) - Wang, Tie; Xiong, Bo; Jin, Zhenghua; Zhang, Haiyan; Chen, Xinlian; Fang, Qi; Zhou, Qianfei; Tian, Zheng; Chen, Mingrong; Wang, Jun; Sun, Guochao; Wang, Zhihui
Abstract: In this experiment, 'Huangguogan' introduced from Shimian to Jiangyou was used as the materialand Shimian 'Huangguogan' as the reference. The adaptability of 'Huangguogan' was studied from three aspects: site climate conditions, basic indicators of tree bodyand fruit quality. The results showed that the overall situation of Shimian 'Huangguogan' was better than Jiangyou 'Huangguogan', especially the internal quality of the fruit, which indicated that Jiangyou was not suitable to introduce 'Huangguogan'.